Prediction of habitat suitability for the desert monitor (Varanus griseus caspius) under the influence of future climate change. (March 2021) - Shadloo, Shabnam; Mahmoodi, Shirin; Hosseinzadeh, Mahboubeh Sadat; Kazemi, Seyed Mahdi
Abstract: Varanus griseus caspius (desert monitor) is a predator included appendix I of Convention on International Trade in Endangered Species; therefore, it is crucial to plan for its conservation. In this study, the suitable habitats of the desert monitor, Varanus griseus caspius, were evaluated in Iran, considering 10 environmental factors, for three periods of time: mid-Holocene, current, and years 2041–2060. Three individual models were produced to create an ensemble model: Generalized Boosting Model (GBM), Generalized Additive Model (GAM), and Random Forests (RF). Next, highly suitable areas in current and future periods were compared to the boundaries of conservation areas (CA). Among the different models projected, the ensemble model performed the best. The results indicated that so far, the distribution range of the species has shifted profoundly and will continue to grow in the future, while some currently suitable CAs will turn into unsuitable habitats for the species. We suggest further studies focus on redefining and broadening the CAs borders. Also, studying the species connectivity in current and potential future habitats can help to protect the species. Highlights: Precipitation and temperature profoundly shape the desert monitor's habitat in Iran. Suitable habitats for the Varanus griseus caspius will increase in the future. Iran's conservation areas will be inadequate to protect the desert monitor in 2050. In the future the species has the potential to move towards western Iran.